Internet of Things’ sustainability effects: quantile and temporal insights - Chao Li; Wenyu Lao (Humanities & Social Sciences Communications)
Abstract As an important technological advancement driving the fourth industrial revolution, the Internet of Things (IOT) has gained increasing attention for its profound economic and societal impacts. However, in the context of escalating challenges in climate change, its effects on environmental sustainability await systematic analysis. Therefore, this paper aims to thoroughly analyze these effects and explore how to promote sustainability more effectively in the process of advancing applications of IOT. This paper employs the Multiscale Wavelet-Based Quantile-on-Quantile approach to investigate the dynamic impact of IOT on sustainability from the perspectives of carbon emissions and air quality across different quantile levels. Results demonstrate that IOT generally exerts negative effects on carbon emissions, which are particularly pronounced in the higher quantiles of emissions. However, this impact is not significant at lower development levels of IOT while reducing carbon emissions as the technology matures. From a dynamic perspective, in the short term, the impact of IOT on carbon emissions is not significant. Nevertheless, in the medium to long term, its carbon reduction effect becomes increasingly pronounced. In comparison, IOT’s impact on air pollution is more heterogeneous. At lower pollution levels, IOT tends to improve air quality, whereas at higher quantiles of pollution, IOT exacerbates it. Besides, the negative effect of IOT on air quality becomes gradually apparent in the medium term, while insignificant in the short term. In the long run, IOT’s influence on air pollution fluctuates significantly. These findings suggest that flexible, scientific, and targeted measures should be scientifically formulated accounting for regional variations and development stages to advance sustainability in applying IOT.